TEMPAT REKREASI DI KAWASAN PURI INDAH - Heriyanto Heriyanto; Agustinus Sutanto (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
In the book "The Great Good Place" written by Ray Oldenburg in 1990. In this book Oldenburg divides the place, where humans live their daily lives, into three namely first place, second place, and third place. First place according to Oldenburg is home, second place is a place to work, and third place is a place to relax (hangout) and socialize. For urban communities who are generally individualistic, third place becomes a kind of necessity, where in those places they have the opportunity to enjoy social relations with other people in a relaxed atmosphere. Site Location located in Puri Indah Area, including CBD (Central Business District) where many work employees who face work tasks that make it stressful. So the purpose of the project is to build a place of relaxation for employees and visitors of the lippo mall to take the time to relax Relaxing, boredom and fatigue and also as a counter-activity subsistence. Field survey results and environmental footprint analysis results. The project entitled "Recreation Places in the Puri Indah Area" / "Recreation Place At Puri Indah" has a building programmatic program, namely: 1) Trampoline Arena 2) Public Market. 3) Food Hall. Trampoline arena provide fun recreational activities with the concept of Tetris Where Activities follow Form.2) public market where public places are open which activities Buy and sell, socializing activities between sellers and buyers. 3) food hall provides open seating where employees can work in a discussion in the food hall. Abstrak Pada Dalam buku “The Great Good Place” yang ditulis oleh Ray Oldenburg pada tahun 1990. Dalam buku ini Oldenburg membagi place, dimana manusia menjalani kehidupan sehari-harinya, menjadi tiga yaitu first place, second place, dan third place.Menurut Ray Oldenburg, Tempat Pertama (First place) adalah rumah, Tempat Kedua(Second place) adalah tempat bekerja atau sekolah, dan Tempat Ketiga(Third place) adalah tempat bersantai (hangout) dan bersosialisasi. Bagi masyarakat perkotaan yang umumnya bersifat individualis, third place menjadi semacam kebutuhan, dimana di tempat-tempat tersebut mereka memiliki kesempatan menikmati hubungan sosial dengan orang lain dalam suasana yang santai.Lokasi Tapak yang terletak Di kawasan Puri Indah Termasuk Kawasan CBD(Central Business District)dimana banyak pegawai kerja yang menghadapi kerjaan tugas yang membuatnya stress.sehingga Tujuan dari proyek adalah untuk membangun satu wadah tempat relaksasi bagi pegawai kerja maupun pengunjung yang dari lippo mall meluangkan waktu kosong untuk berelaksasi Pelepas lelah, kebosanan dan kepenatan dan juga Sebagai imbangan subsisten activity.berdasarkan hasil Survey lapangan dan hasil Analisa lingkungan tapak.proyek yang berjudul “Tempat Rekreasi Di Kawasan Puri Indah”/”Recreation Place At Puri Indah” mempunyai programmatik bangunan yaitu:1)Trampoline Arena 2)Public Market.3)Food Hall.Trampoline arena yang memberi Fasilitas Aktivitas Rekreasi yang menyenangkan dengan konsep Tetris Dimana Aktivitas mengikuti Form.2)publik market dimana tempat publik umum terbuka yang beraktivitas Berjualan-beli,aktivitas bersosialisasi antar penjual dan pembeli.3)food hall menyediakan tempat duduk terbuka dimana pegawai kerja dapat melakukan Berdiskusi di dalam food hall.